CHARACTERIZATION OF 3D-PRINTING FILAMENT WITH EXTRUDER MELTING TEMPERATURE VARIATION FOR BONE IMPLANT FROM KUPANG SHELL - Ananda Maulidha Kusumastuti; Adik Roni Setiawan; Asalina Putri Agung Shaliha; Deden Eko Wiyono; Achmad Ferdiansyah Pradana Putra (Institut Teknologi Adhi Tama Surabaya, 2021)
The number of bone damage in Indonesia continues to increase. Bone implant is one of the medical treatment methods performed on bone damage. Organic and non-organic materials can be used as bone implants. Non-organic materials are stronger, but not biocompatible, while organic materials are biocompatible, but brittle. The addition of polycaprolactone polymer (PCL) can increase the mechanical strength of 3D printing bone implant filaments. Extruder melting temperature is one of the factors that affect the quality of PCL-HAp filaments for bone implants. Studies related to temperature variations in PCL-HAp materials have not been widely studied. Therefore, it is necessary to characterize 3D printing filaments with variations in the melting temperature of the extruder as bone implants from mussel shells with temperature variables of 65oC, 75oC, and 85oC. From this study, the optimum point was found at the melting extruder temperature of 75oC with the results of a diameter of 1.810 and mechanical strength which showed an increase in tensile strength and Young's modulus of PCL-HAp composite in all variables compared to pure PCL. The SEM test showed a rough surface on the filaments that could increase the proliferation and adhesion of good cells for the growth of bone tissue.